Multilingual Turn and the Need of Multilingual Education in the Nepalese Context - Jora, Man Bahadur (Sotang, Yearly Peer Reviewed Journal, 2020)
This article is related with multilingual turn, multilingual education, and the need of it in the Nepalese context. It has highlighted the shifting of monolingual trend into multilingual education. Multilingual turn is a revolution in the sector of education. Day by day the demands of it are increasing for minority and indigenous languages. Similarly, there is need of multilingual education for people from such groups. Accordingly, the need of multilingual education is the focal point of this article. It has linked multilingual turn with multilingual education in the context of Nepal. Multilingual education is significant for learners’ cognitive and literacy skills. These skills are possible through the implication of this type of education. The language learning through the access of home language, or mother tongue is better and more effective for language learners. In true sense, multilingual education is bridging between learners’ first language and target language. Therefore, linguistic diversity is flourished via multilingual education. Nepal, a multilingual country, has linguistic diversity requires multilingual education.